Erratum: PEDRO DÍAZ JIMÉNEZ, THOMAS B. CROAT, JONATHAN D. AMITH, MIGUEL ÁNGEL PÉREZFARRERA & PEDRO A. AGUILAR-RODRÍGUEZ (2024) A new species of broad-leafed Anthurium (Araceae) from the central region of Veracruz, Mexico Phytotaxa 644 (1): 63–68. - Jiménez, Pedro Díaz; Croat, Thomas B.; Amith, Jonathan D.; Pérezfarrera, Miguel Ángel; Aguilarrodríguez, Pedro A. (Phytotaxa, 2024)
Erratum